Soft transition between subcritical and supercritical currents through intermittent cascading interfacial instabilities - Salinas, Jorge (2020)
Long-running gravity currents are flows that are submerged beneath a deep layer of quiescent fluid and they travel over long distances along inclined or horizontal surfaces. They are driven by the density difference between the current and the clear ambient fluid above. In this work we present results on highly resolved direct numerical simulations of turbid underflows that involve nearly 1 billion degrees of freedom. We assess the effect of bed slope on the flow statistics. We explore the turbulence dynamics of the interface in the classical sub-A nd supercritical regimes. We investigate the structure of interfacial turbulence and its relation to the turbulence statistic. A transcritical regime is identified where intermittent cascading interfacial instabilities appear. We investigate how departure from the self-sustaining equilibrium state may be the mechanism responsible for this cyclic evolution of the transcritical regime.